The Impact of Health Insurance on Stockholding: A Regression Discontinuity Approach - Dimitris Christelis; Dimitris Georgarakos; Anna Sanz-de-Galdeano (Institute for the Study of Labor (IZA), 2014)
Using data from the US Health and Retirement Study, we study the causal effect of increased health insurance coverage through Medicare and the associated reduction in health-related background risk on financial risk-taking. Given the onset of Medicare at age 65, we identify our effect of interest using a regression discontinuity approach. We find that getting Medicare coverage induces stockholding for those with at least some college education, but not for their less-educated counterparts. Hence, our results indicate that a reduction in background risk induces financial risk-taking in individuals for whom informational and pecuniary stock market participation costs are relatively low.
Keywords: D14; I13; G11; 330; health insurance; Medicare; stockholding; regression discontinuity; household finance